Arcadian modernism and national identity: The ‘Murdoch press’ and the 1939 Australian Herald ‘Exhibition of French and British Contemporary Art’ - Baker, Janice (Museum and Society, 2015)
The 1939 Australian ‘Herald’ Exhibition of French and British Contemporary Art is said not only to have resonated ‘in the memories of those who saw it’ but to have formed ‘the experience even of many who did not’ (Chanin & Miller 2005: 1). Under the patronage of Sir Keith Murdoch, entrepreneur and managing director of the Melbourne ‘Herald’ newspaper, and curated by the Herald’s art critic Basil Burdett, the exhibition attracted large and enthusiastic audiences. Remaining in Australia for the duration of the War, the exhibition of over 200 European paintings and sculpture, received extensive promotion and coverage in the ‘Murdoch press’. Resonating with an Australian middle-class at a time of uncertainty about national identity, this essay explores the exhibition as an ‘Arcadian’ representation of the modern with which the population could identify. The exhibition aligned a desire to be associated with the modern with a restoration of the nation’s European heritage. In its restoration of this continuity, the Herald exhibition affected an antiquarianism that we can explore, drawing on Friedrich Nietzsche’s insights into the use of traditional history.